"Do no harm" - Where to place remifentanil for labour analgesia?. (December 2017) - Melber, Andrea Anna; Sia, Alex Tiong Heng
Highlights: Remifentanil PCA is arguably the second most effective analgesic method in labour after neuro-axial analgesia. Remifentanil PCA has not had long-term sequelae described so far. It is not hazardous to the environment or medical staff. The unique metabolism of remifentanil into inactive products without accumulation presents a benefit over other opioids. It is associated with the risk of respiratory suppression in the mother and neonate which implies strict safety standards.